Tn5AraOut mutagenesis for the identification of Yersinia pestis genes involved in resistance towards cationic antimicrobial peptides - Guo, Jitao (2011)
Bacterial pathogens display a variety of protection mechanisms against the inhibitory and lethal effects of host cationic antimicrobial peptides (CAMPs). To identify Yersinia pestis genes involved in CAMP resistance, libraries of DSY101 (KIM6 caf1 pla psa) minitransposon Tn5AraOut mutants were selected at 37°C for resistance to the model CAMPs polymyxin B or protamine. This approach targeted genes that needed to be repressed (null mutations) or induced (upstream P(BAD) insertions) for the detection of CAMP resistance, and predictably for improved pathogen fitness in mammalian hosts. Ten mutants demonstrated increased resistance to polymyxin B or protamine, with the mapped mutations pointing towards genes suspected to participate in modifying membrane components, genes encoding transport proteins or enzymes, or the regulator of a ferrous iron uptake system (feoC). Not all the mutants were resistant to both CAMPs used for selection. None of the polymyxin B- and only some protamine-resistant mutants, including the feoC mutant, showed increased resistance to rat bronchoalveolar lavage fluid (rBALF) known to contain cathelicidin and β-defensin 1. Thus, findings on bacterial resistance to polymyxin B or protamine don't always apply to CAMPs of the mammalian innate immune system, such as the ones in rBALF.